Identification of microRNAs in exosomes isolated from serum and umbilical cord blood, as well as placentomes of gestational day 90 pregnant sheep. Issue 11 (30th September 2014) - Cleys, Ellane R.; Halleran, Jennifer L.; McWhorter, Erin; Hergenreder, Joanna; Enriquez, Vanessa A.; da Silveira, Juliano C.; Bruemmer, Jason E.; Winger, Quinton A.; Bouma, Gerrit J.
SUMMARY Despite reports that circulating levels of maternal serum exosomes increase during pregnancy and that placenta‐specific microRNAs (miRNAs) have been identified in humans, little is known about exosomes and miRNAs during pregnancy in agriculture animals. In this study, we characterized the expression of 94 miRNAs in ovine placentomes at gestation day (GD) 90 by real‐time PCR, and then investigated the presence of these miRNAs in exosome samples isolated from maternal jugular blood in non‐pregnant ewes and at GD30 and GD90 and in umbilical blood collected at GD90. In maternal jugular exosome samples, 13 miRNAs were present in lower and 12 miRNAs were present in higher amounts at GD90 compared to non‐pregnant (GD0) or GD30. Additionally, 12 miRNAs were present in higher amounts in umbilical venous exosomes compared to umbilical arterial exosomes; only miR‐132 was lower in exosomes isolated from umbilical venous blood than from umbilical arterial blood. In placentome samples, miR‐34c and miR135a abundance was higher in cotyledon tissue than in caruncle, while miR‐183 and miR‐379 amounts were higher in caruncle than cotyledon tissue. Only miR‐379 was differentially expressed in all serum exosomes and placentome samples. Pathway analysis predicted that differentially expressed maternal serum exosomal miRNAs target Cellular Growth and Proliferation and Organ Development pathways, while umbilical serum exosomal and placentomes miRNAs were predicted to target cellular development and organismal/embryonic development. Mol. Reprod. Dev. 81: 983–993, 2014. © 2014 Wiley Periodicals, Inc.